Electronic Metal–Support Interactions in Single‐Atom Catalysts1. Issue 13 (5th March 2014) - Hu, Pingping; Huang, Zhiwei; Amghouz, Zakariae; Makkee, Michiel; Xu, Fei; Kapteijn, Freek; Dikhtiarenko, Alla; Chen, Yaxin; Gu, Xiao; Tang, Xingfu
Abstract The synthesis of single‐atom catalysts and the control of the electronic properties of catalytic sites to arrive at superior catalysts is a major challenge in heterogeneous catalysis. A stable supported single‐atom silver catalyst with a controllable electronic state was obtained by anti‐Ostwald ripening. An electronic perturbation of the catalytic sites that is induced by a subtle change in the structure of the support has a strong influence on the intrinsic reactivity. The higher depletion of the 4d electronic state of the silver atoms causes stronger electronic metal–support interactions, which leads to easier reducibility and higher catalytic activity. These results may improve our understanding of the nature of electronic metal–support interactions and lead to structure–activity correlations.